2015
DOI: 10.1080/02692171.2015.1016404
|View full text |Cite
|
Sign up to set email alerts
|

Functional distribution of income, aggregate demand, and economic growth in the Chinese economy, 1978–2007

Abstract: This paper seeks to analyse the relationship between the functional distribution of income, aggregate demand and growth in the Chinese reform economy. For this purpose, the Bhaduri-Marglin Model is used to indicate the theoretical possibility of both profit-led and wage-led growth regimes. Previously, the principal literature on the evolution of factor shares in China was reviewed. The statistical series for the period 1978-2007 are reconstructed to carry out our analysis of the relations between capital share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Model (1) is a simple relation between growth and distribution. The coefficient of LS is negative and statistically significant, showing that the growth regime is profit-led, which echoes the results of Molero-Simarro (2015). Across all specifications in Table 6, the coefficients of LS are all negative; in particular, the absolute value of the coefficient is greater in Model (6), which means that the growth regime became more profit-led from 2003 to 2012.…”
Section: An Empirical Analysissupporting
confidence: 67%
“…Model (1) is a simple relation between growth and distribution. The coefficient of LS is negative and statistically significant, showing that the growth regime is profit-led, which echoes the results of Molero-Simarro (2015). Across all specifications in Table 6, the coefficients of LS are all negative; in particular, the absolute value of the coefficient is greater in Model (6), which means that the growth regime became more profit-led from 2003 to 2012.…”
Section: An Empirical Analysissupporting
confidence: 67%
“…While initial studies have focused on advanced capitalist countries, more recent ones have investigated the demand regimes in emerging ones. Among others, Molero‐Simarro (2015) found that the Chinese economy is profit‐led due to the negative impact of increasing labor share on net exports. Jetin and Kurt (2016) analyzed Thailand using different measures of labor share and found a profit‐led economy.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…Chakrabarti (2006) confirms a positive and strong relationship between saving and investment for 126 countries from 1960 to 2000. Molero-Simarro (2015) shows that Chinese growth has been profit-driven. It shows that the higher propensity to save out of profits than out of wages, as well as the response of investment to a change in profit share, is stronger than that of savings.…”
Section: Proponents' View: Priority On Rapid Growthmentioning
confidence: 99%